Prognostic Value of Transthoracic Echocardiography in Children With Pulmonary Arterial Hypertension - Astrid E. Lammers; Jan Marek; Gerhard‐Paul Diller; Sheila G. Haworth; Shahin Moledina (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Transthoracic echocardiography is part of the regular follow‐up protocol at most pediatric pulmonary arterial hypertension (PAH) centers. We aimed to develop a comprehensive and simple echocardiographic risk stratification for children with PAH. Methods and Results We included 63 children with PAH and a biventricular cardiac anatomy without relevant shunt lesions (60% female patients; mean age, 9.0 years; 42 idiopathic PAH and 21 associated PAH) undergoing a standardized transthoracic echocardiographic assessment. The prognostic value of echocardiographic parameters was assessed using Cox proportional hazards survival analysis and recursive partitioning for classification tree methods. Over a median follow‐up period of 4.0 years, 17 patients died and 4 underwent lung transplantation. Various echocardiographic parameters were associated with the combined endpoint of death and transplantation on univariate analysis. On further analysis, right atrial area (z score) and left ventricular diastolic eccentricity index (LVEId) emerged as robust and independent predictors of transplant‐free survival. Considering mortality alone as an end point, a combination of right atrial area, left ventricular diastolic eccentricity index, and tricuspid annular plane systolic excursion were identified as independent predictors of outcome. Based on these parameters, we propose simple risk scores that can be applied at the bedside without computer assistance. CONCLUSIONS Echocardiographic parameters predict prognosis in children with pulmonary hypertension. A combination of widely available parameters including right atrial area, left ventricular eccentricity index, and tricuspid annular plane systolic excursion emerged as risk stratifiers that await external validation but may assist clinicians determining the prognosis of children with PAH.